2017
DOI: 10.1111/all.13110
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D contributes to mast cell stabilization

Abstract: The data demonstrate that VitD is required to maintain the stability of mast cells. The deficiency of VitD results in mast cell activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 23 publications
(28 reference statements)
1
36
0
1
Order By: Relevance
“…111 For example, 25% and 45% of the phenol used in an original PF sample was substituted with three different types of lignins (pine KL, soda anthraquinone flax lignin and sulphonated SKL). 112,113 As such in their effort to synthesize lignin based PF adhesives Jin and his group used enzymatic hydrolysis lignin (EHL), which had a comparatively low molecular weight (900 -1300 g/mol). Three of the above-mentioned samples (45% soda anthraquinone flax lignin based novolac, 25% sulfonated SKL based novolac and 45% sulfonated SKL based novolac) showed a single T g , positioned well between the T g s of the pure lignin and the commercial PF resin samples.…”
Section: -100mentioning
confidence: 99%
“…111 For example, 25% and 45% of the phenol used in an original PF sample was substituted with three different types of lignins (pine KL, soda anthraquinone flax lignin and sulphonated SKL). 112,113 As such in their effort to synthesize lignin based PF adhesives Jin and his group used enzymatic hydrolysis lignin (EHL), which had a comparatively low molecular weight (900 -1300 g/mol). Three of the above-mentioned samples (45% soda anthraquinone flax lignin based novolac, 25% sulfonated SKL based novolac and 45% sulfonated SKL based novolac) showed a single T g , positioned well between the T g s of the pure lignin and the commercial PF resin samples.…”
Section: -100mentioning
confidence: 99%
“…The immunomodulatory activity of vitamin D seems to work also for those cells having a major role in the allergic response, such as mast cells, as vitamin D participates in stabilizing their function, whereas its deficiency should promote the activation of these cells. 172,173 The immunoregulatory role of vitamin D in mast cell-mediated allergy is assessed by the ability of these leukocytes to express enzymes able of activating the vitamin D biochemical pathway, such as CYP27A1 and CYP27B1. 174,175 Most probably, mast cells are able to activate 1α,25 (OH) 2 D 3 vitamin from the precursor 25OHD 3 via the CYP27B1 activity, thus dampening immunoglobulin E-mediated hypersensitivity, a mechanism that has also been reported for adipocytes.…”
Section: Role In Acquired and Regulatory Immunitymentioning
confidence: 99%
“…Mast cells are well known to be required in allergen-induced diarrhea (22)(23)(24). As it has been reported that vitamin D3 suppressed the mast cell activation (25,26), we presume that cholecalciferol might also possibly control the allergic diarrhea through the suppressive effect on mast cells in addition to that on CD4 1 T cells in our model. In addition, several studies reported that mast cells could express CD69 on the cell surface in some situations (27,28).…”
Section: Discussionmentioning
confidence: 70%